Molecular magnetisabilities computed via finite fields: assessing alternatives to MP2 and revisiting magnetic exaltations in aromatic and antiaromatic species. (17th November 2021) - Stauch, Tim; Ganoe, Brad; Wong, Jonathan; Lee, Joonho; Rettig, Adam; Liang, Jiashu; Li, Jie; Epifanovsky, Evgeny; Head-Gordon, Teresa; Head-Gordon, Martin
Abstract : Magnetic properties of molecules such as magnetisabilities represent second-order derivatives of the energy with respect to external perturbations. To avoid the need for analytic second derivatives and thereby permit evaluation of the performance of methods where they are not available, a new implementation of quantum chemistry calculations in finite applied magnetic fields is reported. This implementation is employed for a collection of small molecules with the aug-cc-pVTZ basis set to assess orbital optimised (OO) MP2 and a recently proposed regularised variant of OOMP2, called κ -OOMP2. κ -OOMP2 performs significantly better than conventional second-order Møller–Plesset (MP2) theory, by reducing MP2's exaggeration of electron correlation effects. As a chemical application, we revisit an old aromaticity criterion called magnetisability exaltation. In lieu of empirical tables or increment systems to generate references, we instead use straight chain molecules with the same formal bond structure as the target cyclic planar conjugated molecules. This procedure is found to be useful for qualitative analysis, yielding exaltations that are typically negative for aromatic species and positive for antiaromatic molecules. One interesting species, N 2 S 2, shows a positive exaltation despite having aromatic characteristics. GRAPHICAL ABSTRACT: UF0001